CD151 Promotes Proliferation and Migration of PC3 Cells via the Formation of CD151-integrin α3/α6 Complex - 杨五小 李鹏程 林敬阳 左后娟 左萍 邹远林 刘正湘 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
Over-expression of CD151 was found to be associated with metastasis and poor prognosis of prostatic carcinoma. This study was designed to examine the mechanism by which CD151 promotes the proliferation and migration of prostatic cancer cells. The pAAV-CD151, pAAV-GFP and pAAV-CD151-AAA mutant plasmids were constructed and used to transiently transfect PC3 cells （a prostatic carcinoma 3 cell line） by the mediation of Fugene HD. Then, the cells were assigned to control group, pAAV-GFP group, pAAV-CD151 group, and pAAV-CD151-AAA group respectively. Cell proliferation was evaluated by using the 3-[4,5-dimet-hylthiazol-2-yl]-2,5, diphenyltetrazolium bromide （MTT） method. Cell migration assay was performed by using Boyden chambers. The formation of CD151-integrin a3/a6 complex was determined by the method of co-immunoprecipitation. The protein expression levels of CD151 and extracellular signal-regulated kinase （ERK） were measured by Western blotting. The results showed that transfection of pAAV-CD151 or pAAV-CD151-AAA mutant increased the expression of CD151 protein in PC3 cells. Co-immunoprecipitation showed that more CD151-integrin a3/a6 complex was formed in the pAAV-CD151 group than in the control group, the pAAV-GFP group and the pAAV-CD151-AAA mutant group. Furthermore, the proliferative and migrating capacity of PC3 cells was substantially increased in the pAAV-CD151 group but inhibited in the pAAV-CD151-AAA mutant group. CD151 transfection increased the expression of phospho-ERK. Taken together, it was concluded that CD151 promotes the proliferation and migration of PC3 cells through the formation of CD151-integrin complex and the activation of phosphorylated ERK.